2022
DOI: 10.1038/s41598-022-12025-7
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant production by Bacillus subtilis SL and its potential for enhanced oil recovery in low permeability reservoirs

Abstract: Microbial enhanced oil recovery (MEOR) technology is an environmental-friendly EOR method that utilizes the microorganisms and their metabolites to recover the crude oil from reservoirs. This study aims to research the potential application of strain SL in low permeability reservoirs. Strain SL is identified as Bacillus subtilis by molecular methods. Based on the mass spectrometry, the biosurfactant produced by strain SL is characterized as lipopeptide, and the molecular weight of surfactin is 1044, 1058, 1072… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…These results are of growing interest as the prospective application of BioS in numerous industrial processes necessitates thermal stabilities. Previous research works exhibited similar findings(Chen et al 2017;Ghazala et al 2017;Kiran et al 2017;Martins et al 2018;Feng et al 2019;Purwasena et al 2019;Zouari et al 2019;Jimenez et al 2021;Mnif et al 2021aMnif et al , 2021bUmar et al 2021;Wu et al 2022).…”
supporting
confidence: 77%
See 3 more Smart Citations
“…These results are of growing interest as the prospective application of BioS in numerous industrial processes necessitates thermal stabilities. Previous research works exhibited similar findings(Chen et al 2017;Ghazala et al 2017;Kiran et al 2017;Martins et al 2018;Feng et al 2019;Purwasena et al 2019;Zouari et al 2019;Jimenez et al 2021;Mnif et al 2021aMnif et al , 2021bUmar et al 2021;Wu et al 2022).…”
supporting
confidence: 77%
“…As shown in Figure 3(c), the BioS of MI27 shows a maximum emulsification of around 45%, which is obtained at concentrations greater than or equal to 1,000 mg/L. In this aim, numerous bacterial-derived surfactin, exhibited emulsification activities of around 67.6% for those derived from B. subtilis isolate LSFM-05 (de Faria et al 2011), around 98% as reported by Long et al (2017), around 55% for surfactin-like BioS produced by novel strain B. nealsonii S2MT (Phulpoto et al 2020), between 58 and 64% for B. subtilis #309 derived surfactin (Janek et al 2021) and between 56, 67, 54 and 60% for B. subtilis LS-derived surfactin isoforms (Wu et al 2022). This emulsification property makes BioS excellent candidates for the bioremediation of water and soil contaminated with oils and hydrocarbons (Maier & Soberon 2000).…”
Section: Study Of Emulsification Activitymentioning
confidence: 89%
See 2 more Smart Citations
“…Microbial enhanced oil recovery (MEOR) attracts broad attention with the advantages of environment-friendliness and low-cost ( Wu et al., 2022 ). Microbial enhanced oil recovery (MEOR) is one of the tertiary oil recovery approaches which uses ex-situ/in-situ microorganisms and their metabolites like biopolymers, biosurfactants, bio-enzymes, biogases, solvents, and biogenic acids to modify the flow characteristics of residual oil in the reservoirs to enhance oil recovery ( Niu et al., 2020 ; Patel et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%